Synthesis of 1,2-Di(phenyl)ethan-1,2-dione through Oxidation of 2-Hydroxy-1,2-Dipheniletanone by using Copper(II) Citrate - Seviani, Winda; Fadlan, Arif; Wirastuti, Vania (Departemen Kimia, 2025)
1,2-Di(phenyl)-1,2-dione widely used in chemical and pharmaceutical industries and found as a framework in secondary metabolites can be obtained through oxidation of 2-hydroxy-1,2-diphenylethanone using strong acids, homogeneous, heterogeneous, and metal catalysts. However, these oxidation methods exhibit various drawbacks. This study reported the oxidation of 2-hydroxy-1,2-diphenylethanone by using copper(II) citrate to produce 1,2-di(phenyl)-1,2-dione. The oxidation performed with copper(II) citrate and ammonium nitrate in glacial acetic acid as solvent yielded 1,2-di(phenyl)-1,2-dione in 88% yield higher than the nitric acid method (79% yield). The FTIR, NMR spectriscopies, and mass analysis confirmed the structure of 1,2-di(phenyl)ethane-1,2-dione. The oxidation of 2-hydroxy-1,2-diphenylethanone using copper(II) citrate is proposed by the formation of Cu⁺ ions and a resonance-stabilized 2-hydroxy-1,2-diphenylethanone radical resulting in 1,2-di(phenyl)ethane-1,2-dione.